Exogenous Application of 5-Aminolevulinic Acid Promotes Coloration and Improves the Quality of Tomato Fruit by Regulating Carotenoid Metabolism - Wang, Junwen; Zhang, Jing; Li, Jing; Dawuda, Mohammed Mujitaba; Ali, Basharat; Wu, Yue; Yu, Jihua; Tang, Zhongqi; Lyu, Jian; Xiao, Xuemei; Hu, Linli; Xie, Jianming (Frontiers in Plant Science, 2021)
5-Aminolevulinic acid (ALA) plays an important role in plant growth and development. It can also be used to enhance crop resistance to environmental stresses and improve the color and internal quality of fruits. However, there are limited reports regarding the effects of ALA on tomato fruit color and its regulatory mechanisms. Therefore, in this study, the effects of exogenous ALA on the quality and coloration of tomato fruits were examined. Tomato (Solanum lycopersicum ‘Yuanwei No.1’) fruit surfaces were treated with different concentrations of ALA (0, 100, and 200 mg·L-1) on the 24th day after fruit setting (mature green fruit stage), and the content of soluble sugar, titratable acid, soluble protein, vitamin C, total free amino acids, as well as 11 kinds of free amino acid components, intermediates of lycopene synthetic and metabolic pathways, and ALA metabolic pathway derivatives were determined during fruit ripening. The relative expression levels of genes involved in lycopene synthesis and metabolism and those involved in ALA metabolism were also analyzed. The results indicated that exogenous ALA (200 mg·L-1) increased the contents of soluble sugars, soluble proteins, total free amino acids, and vitamin C in tomato fruits and reduced the content of titratable acids, thus improving the quality of tomato fruits harvested 4 days earlier than those of the control plants. In addition, exogenous ALA markedly improved carotenoid biosynthesis by upregulating the gene expression levels of geranylgeranyl diphosphate synthase (GGPPS), phytoene synthase 1 (PSY1), phytoene desaturase (PDS), and lycopene β-cyclase (LCY-B). Furthermore, exogenous ALA inhibited chlorophyll synthesis by downregulating the genes expression levels of Mg-chelatase (CHLH) and protochlorophyllide oxidoreductase (POR). These findings suggest that supplementation with 200 mg·L-1 ALA not only enhances the nutritional quality and color of the fruit but also promotes early fruit maturation in tomato.